Skilled Immigration, Task Allocation and the Innovation of Firms - Anna Maria Mayda; Gianluca Orefice; Gianluca Santoni (Institute of Labor Economics (IZA), 2022)
This paper analyses the impact of skilled migrants on the innovation (patenting) activity of French firms between 1995 and 2010, and investigates the underlying mechanism. We present districtlevel and firm-level estimates and address endogeneity using a modified version of the shift-share instrument. Skilled migrants increase the number of patents at both the district and firm level. Large, high-productivity and capital-intensive firms benefit the most, in terms of innovation activity, from skilled immigrant workers. Importantly, we provide evidence that one channel through which the effect works is task specialization (as in Peri and Sparber, 2009). The arrival of skilled immigrants drives French skilled workers towards language-intensive, managerial tasks while foreign skilled workers specialize in technical, research-oriented tasks. This mechanism manifests itself in the estimated increase in the share of foreign inventors in patenting teams as a consequence of skilled migration. Through this channel, greater innovation is the result of productivity gains from specialization.
Keywords: F22; J61; 330; skilled immigration; innovation; patents